Implementation Discovery Learning Model in Arabic Free Writing - Farida Fauziah; Saefudin Saefudin; Amin Al Masyhuri; Muhammad Ilyas Alkayisy (Tadris Al-'Arabiyyah: Jurnal Pendidikan Bahasa Arab dan Kebahasaaraban, 2025)
Arabic writing skills are essential for comprehensive language mastery. However, teaching free writing often faces challenges, including less engaging methods and learning models. This research aims to identify effective learning models, key elements, and obstacles encountered in teaching Arabic free writing skills. Free writing is the culminating stage in developing Arabic writing skills, encompassing expressing thoughts and feelings using appropriate vocabulary and grammar. Employing a qualitative approach with descriptive and analytical designs, data is collected through interviews, observations, and document analysis. The results reveal that the applied learning model is structured from objective setting to evaluation, focusing on students' ability to write grammatically correct sentences. Learning material, themed "Introduction," is delivered via dictation, with evaluation through free writing tests. Motivation emerges as a vital element. Obstacles include varied educational backgrounds and limited resources. This research provides insights for educators and curriculum developers, offering a structured and comprehensive learning model and identifying crucial motivational elements to enhance Arabic free writing skills. A well-defined pedagogical model, encompassing clear objectives, relevant materials, and appropriate assessment techniques, is necessary to foster effective free writing skills among students, as is considering motivational factors to engage students in the learning process and overcome potential challenges.